Detection of chromite minerals using Spectral Linear Unmixing on Sentinel-2 imagery. Case study: Ingessana Hills, Blue Nile Province, Sudan - Anifanti, A.; Sykioti, O.; Vassilakis, Emm. (15th International Congress of the Geological Society of Greece, 2019)
The Ingessana hills in the southern Blue Nile of Sudan consist of serpentinised and highly silicified dunites in contact with the intruding Bau granite. The observed chromite mineralization zones are associated with NE-SW trending shear-zones. The mineralization associated with ophiolitic belts includes podiform chromite, asbestos, talc, and base metal (Cu, Ni, Co) mineralization. We applied Linear Spectral Unmixing algorithm on a 10m spatial resolution Sentinel-2 images in order to detect and map the chromite mineralization and the associated mineralization of ophiolitic belts. The resulting abundance maps show the capability of Sentinel-2 for detailed mineral mapping and detection of potential chromite ore deposit locations.